Influence of product quality and perceived value on customer catisfaction and loyalty in clinical skincare products: English - Ariztian, Rian; Ramli, Abdul Haeba (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the influence of Product Quality and Perceived Value on Customer Satisfaction and their implications for Customer Loyalty among users of clinical skincare products in Serang City. The research method used a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis techniques, involving 195 respondents. The results indicate that Product Quality and Perceived Value have a positive influence on Customer Satisfaction. Furthermore, Customer Satisfaction has been shown to contribute to increasing Customer Loyalty. Furthermore, Product Quality and Perceived Value also directly influence Customer Loyalty. These findings strengthen the evidence that a satisfying user experience and perceived value play a crucial role in fostering customer loyalty. Managerial implications suggest that beauty clinics need to prioritize improving product quality and perceived customer value to maintain loyalty. This study is limited by the region and the dominance of a single brand in the sample. Therefore, further research is recommended with a broader scope and involving a variety of clinical skincare brands